Environmental predictors of SARS-CoV-2 infection incidence in Catalonia (northwestern Mediterranean) - Planella-Morató, Jesús; Pelegrí, Josep L.; Martín-Rey, Marta; Olivé Abelló, Anna; Vallès, Xavier; Roca, Josep; Rodrigo, Carlos; Estrada, Oriol; Vallès-Casanova, Ignasi (Frontiers in Public Health, 2024)
Numerous studies have explored whether and how the spread of the SARS-CoV-2, the causative agent of coronavirus disease 2019 (COVID-19), responds to environmental conditions without reaching consistent answers. Sociodemographic factors, such as variable population density and mobility, as well as the lack of effective epidemiological monitoring, make it difficult to establish robust correlations. Here we carry out a regional cross-correlation study between nine atmospheric variables and an infection index (Ic) estimated from standardized positive polymerase chain reaction (PCR) test cases. The correlations and associated time-lags are used to build a linear multiple-regression model between weather conditions and the Ic index. Our results show that surface pressure and relative humidity can largely predict COVID-19 outbreaks during periods of relatively minor mobility and meeting restrictions. The occurrence of low-pressure systems, associated with the autumn onset, leads to weather and behavioral changes that intensify the virus transmission. These findings suggest that surface pressure and relative humidity are key environmental factors that may be used to forecast the spread of SARS-CoV-2.